Grumpy monkey : Valentine gross-out - Lang, Suzanne; Lang, Max, 1982- (New York : Random House Studio, 2022)
"Jim Panzee is very grumpy about Valentine's Day until his buddy Norman shows him that the holiday is for everyone."--
Accompanying material may vary.
Ages 4-8.
Grades K-1.
AD480L
Decoding demand: 73 (high) Semantic demand: 72 (high) Syntactic demand: 69 (high) Structure demand: 77 (high)
Keywords: Chimpanzees -- Juvenile fiction; Animals -- Juvenile fiction; Valentine's Day -- Juvenile fiction; Mood (Psychology) -- Juvenile fiction; Animal fiction; Picture books